2007
DOI: 10.1097/shk.0b013e31804858f2
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Duct Ligation Abrogates the Trauma Hemorrhage-Induced Gut Barrier Failure and the Subsequent Production of Biologically Active Intestinal Lymph

Abstract: The studies of the mechanisms by which trauma-hemorrhagic shock leads to gut injury and dysfunction have largely ignored the nonbacterial factors contained within the lumen of the intestine. Yet, there is increasing evidence suggesting that intraluminal pancreatic proteases may be involved in this process. Thus, we tested the hypothesis that pancreatic proteases are necessary for the trauma-hemorrhagic shock-induced gut injury and the production of biologically active mesenteric lymph by determining the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Thus ischemia-reperfusion-mediated oxidative modification of the mucus may render the mucus layer susceptible to pancreatic digestive enzymes contained within the gut lumen. This notion is consistent with recent studies showing that pancreatic duct diversion of pancreatic enzymes from the intestinal lumen is associated with amelioration of T/HS-induced gut injury and preservation of both the intestinal mucus layer and gut barrier function (4). Thus, in the absence of pancreatic proteases in the gut lumen, T/HS-induced gut injury and dysfunction, as well as loss of the mucus layer, were largely abrogated.…”
Section: Discussionsupporting
confidence: 80%
“…Thus ischemia-reperfusion-mediated oxidative modification of the mucus may render the mucus layer susceptible to pancreatic digestive enzymes contained within the gut lumen. This notion is consistent with recent studies showing that pancreatic duct diversion of pancreatic enzymes from the intestinal lumen is associated with amelioration of T/HS-induced gut injury and preservation of both the intestinal mucus layer and gut barrier function (4). Thus, in the absence of pancreatic proteases in the gut lumen, T/HS-induced gut injury and dysfunction, as well as loss of the mucus layer, were largely abrogated.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the fact that the duct ligation model prevents pancreatic enzymes from reaching the gut lumen could help explain the lack of microscopic morphologic evidence of gut injury. Further support for the role of luminal pancreatic proteases in exacerbating gut injury comes from studies in a trauma-hemorrhagic shock model where pharmacologic neutralization of luminal pancreatic proteases (34) or pancreatic duct diversion (35) limited gut injury and preserved gut barrier function. On the other hand, our result suggest that the duration and magnitude of the ischemia-reperfusion insult was sufficient to cause injury to the mucus layer as well as loss of gut barrier function, despite the absence of intraluminal pancreatic proteases and evidence of microscopic morphologic gut injury.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal lymph pathway plays an important role in organ injuries in severe pathological conditions, such as hemorrhagic and traumatic shock and acute pancreatitis 5,15 . The report form Sambol et al 8 found that MLDL could prevent trauma/ hemorrhage shock-induced increases in LVDP and ±dP/dt max of isolated hearts form trauma/hemorrhage shocked rats.…”
Section: Discussionmentioning
confidence: 99%